IMPLEMENTATION OF ISLAMIC EDUCATIONAL VALUES IN FORMING STUDENTS' DISCIPLINED CHARACTER - Fathul Amin; Muhaiminah Darajat (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2025)
This study aims to describe the implementation of Islamic educational values in  shaping students’ disciplinary character at Madrasah Tsanawiyah. The research  focuses on the internalization process of aqidah, akhlaq, and ibadah values in  developing students’ disciplined behavior, as well as the disciplinary guidance  strategies applied by teachers and the institution. This study employs a qualitative  approach using a descriptive method. Data were collected through observation,  interviews, and documentation, and analyzed using data reduction, data display,  and conclusion drawing techniques. The findings reveal that Islamic educational  values play an important role in shaping students’ disciplinary character through  Islamic Religious Education learning, habituation of religious activities, and  teacher role modeling. Disciplinary guidance strategies are carried out through  persuasive and humanistic approaches, such as providing rewards, positive  reinforcement, rule reminders, personal counseling, and implementation of  educational consequences. This approach aligns with Bandura’s social learning  theory on behavioral modeling and Skinner’s reinforcement theory emphasizing the  importance of positive reinforcement. The implementation of Islamic educational  values is proven effective in developing students’ discipline in terms of punctuality,  adherence to school regulations, academic responsibility, and consistency in  performing worship.